Immunoblots and plasmid fingerprints compared with serotyping and polyacrylamide gel electrophoresis for typing Clostridium difficile. - Mulligan, M E (1988)
Two new methods for typing Clostridium difficile, immunoblotting and plasmid fingerprinting, were compared with serotyping and polyacrylamide gel electrophoresis (PAGE). Of these methods, immunoblotting was found to be the most valuable for use in a comprehensive typing system. More groups could be distinguished by immunoblotting than by serotyping or PAGE. Immunoblotting results were also more reproducible and distinctive than results by PAGE. Plasmid fingerprinting was an excellent marker for plasmid-bearing strains, but it had limited use because many isolates lacked plasmids. A unique plasmid profile observed for one group of isolates correlated with differences in phenotypic characteristics resolved by immunoblot analysis but not by serotyping or PAGE. Preliminary attempts to correlate typing results with pathogenicity of isolates were not successful but underscored the need for future studies to include careful assessment of the clinical significance of isolates.